PROGRAMA DE ATENÇÃO AO IDOSO: A EXPERIÊNCIA DE UM MODELO ASSISTENCIAL - Oliveira, Karla R. d.; Berlezi, Evelise M.; Eickhoff, Heloisa M.; Huth, Adriane; Bonfada, Sonia T.; Bueno, Cristiane S.; Pillatt, Ana P. (Salão do Conhecimento, 2013)
Resumo